Travelling in the Classroom: Podcasting as an Active-Learning Tool for Interdisciplinarity - Diphoorn, Tessa; McGonigle Leyh, Brianne (Journal of Interdisciplinary Studies in Education, 2023)
Interdisciplinarity in the classroom is predominantly championed around a need to address pressing social problems by integrating knowledge from diverse disciplines. But can interdisciplinary teaching take shape without the usual problem-solving frame? And are there new methods/mediums through which to explore interdisciplinarity? These questions have led to new and promising developments related to podcasting, active learning, and interdisciplinarity in the classroom. Through the lens of Travelling Concepts, we reflect on our experiences in the making and using of the podcast series – Travelling Concepts on Air – to better understand interdisciplinarity. We show the value of students not only listening to podcasts as a supplementary means of learning, but also creating podcasts as a form of active learning